Analisis Penyebab Menurunnya Minat dan Partisipasi Generasi Muda dalam Sektor Pertanian: Analysis of the Causes of Decreasing Interest and Participation of Young Generation in the Agricultural Sector - Oktaviani, Dewi Anggun; Rozci, Fatchur (Jurnal Ilmiah Manajemen Agribisnis, 2023)
This research aims to determine the causes of the decline in the interest and participation of the younger generation in the agricultural sector and its impact, so that appropriate steps can be taken to improve the situation. The research method used is a literature study with a secondary data collection approach from the library by reading, taking notes, and then processing library materials to be used as discussion and research results. The results of the study show that the decline in interest and participation of the younger generation is caused by negative perceptions of agriculture, urbanization, and modernization, limited access to resources, economic uncertainty, level of education, and changes in social and values. This phenomenon can threaten a country's food security and the sustainability of the agricultural sector, so a comprehensive and sustainable strategy is needed, such as increasing education and training, skills development, infrastructure development and access to resources, increasing economic welfare, promotion and campaigning, and building partnerships and collaboration.